The Style of Indonesian Contemporary Art Gallery in West Jakarta - Puspitarini Subagyo; Swambodo Murdariatmo Adi (Institut Seni Indonesia Denpasar, 2023)
Some contemporary art works with regional elements can be used as a tool to introduce and preserve the culture of various tribes in Indonesia. Even so, there are still very few places that serve as 'homes or exhibitions' for works of contemporary art. Therefore, an art gallery is needed that can accommodate, exhibit, and store contemporary art works from all over Indonesia. The design method used is a descriptive-qualitative research method with a rationalistic approach. The descriptive-qualitative research method with a rationalistic approach is expected to be able to analyze the shape of the building, the relationship between the building and the environment, and people's views of the Indonesian Contemporary Art Gallery Building. The Indonesian Contemporary Art Gallery building in West Jakarta can accommodate contemporary art works and is considered a building with high property value. In this case, artists can combine their contemporary works of art with elements of culture and art from all corners of Indonesia.